(untitled) (Medico Legal Update, 2021)
Continuous Ambulatory Peritoneal Dialysis (CAPD) is one of kidney replacement therapy with advantage of home therapy and much cheaper than hemodialysis. Nevertheless, CAPD patients need integrated health care by primary care health facilities to maintain CAPD effectiveness of which has never been assessed and improved. Therefore, this study aims to assess the effect of modified CAPD patient’s handling process among nurses at the primary care level. This quasi-experimental study, 47 nurses in sub-district health promoting hospitals (HPHs) of Nan general hospital renal node which completed the standard protocol were assigned to an experimental group, which received the modified-continuous ambulatory peritoneal dialysis (CAPD) patient’s handling process intervention. The intervention covered both a case management (CM) and a CAPD web-based program. The comparative groups were 45 nurses in sub-district health promoting hospitals of Pua Crown Prince Hospital renal node. The main outcomes were improvement in knowledge, perceived benefits and CAPD patients care performances of which assessed by t-test, and ANCOVA. There were significant higher scores of knowledge, perceived benefits and performances of nurses in the experimental group applying the “Modified CAPD patient’s handling process” than those of the comparative group. Therefore, this intervention should be implemented in other primary care facilities to improve qualities of care for CAPD patients.